2008
DOI: 10.1007/s10551-008-0012-x
|View full text |Cite
|
Sign up to set email alerts
|

Does Stakeholder Management have a Dark Side?

Abstract: causal ambiguity, corporate governance, managerial discretion, stakeholder management, stakeholder theory,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 90 publications
2
102
0
1
Order By: Relevance
“…The evidence-based perspective we adopt in this paper provides insights into the interaction dynamics between internal and external organizational actors in multi-stakeholder involvement processes. Cennamo et al (2009) andGreenwood andVan Burren (2010) point out that these dynamics are missing in stakeholder theory. The combination of identi cation and salience analysis in the contextualization phase and the argumentation construction in the problematization phase led to the creation of successful stakeholder involvement, which constitutes the basis of our research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence-based perspective we adopt in this paper provides insights into the interaction dynamics between internal and external organizational actors in multi-stakeholder involvement processes. Cennamo et al (2009) andGreenwood andVan Burren (2010) point out that these dynamics are missing in stakeholder theory. The combination of identi cation and salience analysis in the contextualization phase and the argumentation construction in the problematization phase led to the creation of successful stakeholder involvement, which constitutes the basis of our research.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of IASs is to bring together a variety of actors, such as businesses, NGOs, UN-system agencies, government entities, and academic institutions (Gilbert et al, 2011). Although scholars have largely debated opportunities and problems related to IAS adoption from a macro-economic and governance perspective, (Gilbert & Rasche, 2007;Mueckenberger & Jastram, 2010;Scherer & Palazzo, 2007), the exact role of stakeholders and related management practices remain overlooked, with little evidence-based understanding of the interaction between internal and external organizational actors in multi-stakeholder involvement processes (Cennamo, Berrone, & Gomez-Mejia, 2009;Gilbert et al, 2011;Greenwood & Van Burren, 2010), despite the fact that a generally relational approach to conceptualizing stakeholders is not new (Freeman, 1984). A large body of research on stakeholder management has largely focused on the mapping of stakeholders in terms of who/what counts to achieve better integration with organizational objectives (Aggeri & Acquier, 2005;Mitchell, Agle, & Wood, 1997;Preble, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In that sense, an important research implication is that the relationship between SEW and firm performance should be examined in the future through possible mediating mechanisms. For instance, Cennamo et al (2012) have suggested that family firm SEW leads to higher proactive stakeholder engagement which limits their ability to innovate and significantly influences firm performance (Cennamo et al, 2009). Given this, future research could examine the mediating role of proactive stakeholder engagement or other variables in the relationship between SEW and performance in family firms.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Furthermore, GIS engagement can yield reputational benefits in the local context where the firm is traditionally embedded. These benefits are especially relevant for family than non-family firms because, in virtue of their greater local embeddedness (Graafland, 2002), family businesses are more dependent on the local context for their survival than their nonfamily counterparts (Clarkson, 1995) and, hence, they strive to gain local legitimacy by building trustworthy relationships with stakeholders (Cennamo et al, 2009;Jones and Wicks, 1999;Laplume et al, 2008). They are committed to project and perpetuate a positive family image and reputation (Westhead et al, 2001).…”
Section: Background Literature and Hypothesesmentioning
confidence: 99%